Connecting bone metastasis, adipose tissue and adipokines: How does physical activity fit? - Paola Maroni; Marta Gomarasca; Michela Signo; Giovanni Lombardi (Advanced Exercise and Health Science)
Cancer has become the leading cause of mortality worldwide, and the spread of metastases represents the most serious aspect of the neoplastic disease. In particular, bone is a primary and recurrent metastatic site for many types of tumours. A link between adipokines, the cytokines and factors derived from adipose tissue, and tumour development and progression has been reported. Adipokines can act systemically or directly on tissues to drive cancer initiation, progression and metastasis. Physical activity has been considered an effective non-pharmacological treatment for many diseases, including obesity and cancer, due to its anti-inflammatory properties. The beneficial effect of physical activity is mediated by adipokines, which can be modulated to exert an anti-inflammatory profile during physical exercise. This review summarises the evidence on how the alteration of adipose tissue is reflected in the release of adipokines and how these molecules may act as mediators of tumour development and progression, especially in the onset of tumour dissemination to the bone. In this regard, physical activity should be implemented in the therapeutic programs for cancer patients, in particular, for those suffering from bone metastases. Although there are safety concerns related to potential skeletal complications or the efficacy of the intervention, exercise has been shown to be beneficial for these patients in terms of improved quality of life, response to treatment, pain management and bone health.